PERENCANAAN DESAIN PERKERASAN DAN GEOMETRI JALAN MASUK DI BANDAR UDARA NGLORAM BLORA - Avrila Bella Soraya; Bambang Wasito; Setyo Hariyadi (Prosiding SNITP (Seminar Nasional Inovasi Teknologi Penerbangan))
Ngloram Airport is located in Cepu District, Blora Regency, Central Java. It has a runway length of 1500 meters x 30 meters. The plan for Ngloram Airport is to be operated in 2021, and it is necessary to improve flight safety and security. Ngloram Air does not yet have an access road which is very important in an airport component in accessing the road to the passenger terminal. Therefore, it is necessary to plan an access road at Ngloram Airport. This planning uses a flexible pavement type with a calculation method. Component analysis, conducts geometric road planning and calculates the Budget Plan (RAB) using the Flexible Road Pavement Thickness Planning Guidelines with the SKBI 2.3.26.1987 Component Analysis Method, in planning work analysis and unit price analysis using the basic unit price of Blora Regency for the fiscal year 2019. From the results of the calculations and data analysis carried out, the length of the 880 m and width 12 m Ngloram Airport access road was obtained, the total thickness of the access road was 40 cm, with details of the surface 5 cm, the base course 15 cm, and the subbase 20 cm. needed for the construction of an access road of Rp Rp4.805.500.000,- (Four Billion Eight Hundred Five Million Five Hundred Thousand Rupiahs).